Bilateral Choroidal Infiltrates as the Initial Manifestation of Waldenström Macroglobulinemia Relapse. (March 2022) - Tan, Jason; Chandra, Varun; Hall, Anthony J.
Purpose: This work describes a case of Waldenström macroglobulinemia (WM) relapse presenting with unilateral blurred vision. Method: A case report is presented. Results: A 60-year-old woman with a history of WM in remission was referred for suspicious peripheral choroidal lesions and left optic disc swelling. Magnetic resonance imaging revealed optic nerve and cranial nerve infiltration consistent with central nervous system invasion from WM relapse, called Bing-Neel syndrome. Irradiation of the optic nerve and systemic targeted therapy were successful in addressing the ocular features as well as reducing immunoglobulin M paraprotein levels and lymphoproliferative disease burden. Conclusions: We described the first documented case to our knowledge of intraocular involvement as the earliest sign of relapse of WM. Ophthalmology assessment is warranted in patients with a history of WM who present with new ocular symptoms to aid early detection and treatment of this disease.